Work-related musculoskeletal disorders in tyre factory workers – An observational study - Anand Heggannavar; Snusha Naik (BLDE University Journal of Health Sciences, 2022)
CONTEXT: Work-related musculoskeletal disorders (WRMSDs) are considered major public health problems and the leading cause of occupational injury. Activities such as prolonged standing, repetitive task, awkward sitting posture, heavy lifting, pulling, and pushing may result in functional impairment and pain due to poor working conditions and absence of work injury prevention programs. AIM: This study aimed to determine the prevalence of WRMSDs in factory workers. SETTINGS AND DESIGN: An observational study was carried out in a tyre factory in India. SUBJECTS AND METHODS: Two hundred and fifty-two (n = 252) male workers aged 21–59 years with at least 1 year of job tenure were included in this observational study. The assessment was done using the Nordic Musculoskeletal Questionnaire and Rapid Entire Body Assessment (REBA) tool. STATISTICAL ANALYSIS USED: Data analysis was done using Chi-square test to calculate the prevalence of musculoskeletal disorders. RESULTS: The most commonly affected body regions of factory workers in 12 months were neck and lower back with P = 0.001and P = 0.146, and problems faced in the past 7 days were more common in the lower back and neck with P = 0.004 and 0.001, respectively. This study reported the highest prevalence in the neck (62.7%) and lower back (54.8%). The REBA tool revealed a majority of the workers emerged under the category of high risk. CONCLUSIONS: The study concluded that neck and lower back regions were found to be more commonly affected, and a majority of workers emerged into high-risk category.